4x-2y+3x+2y When simplified: 7x
It is 16y+23x simplified
x+7x+3y-y =8x+2y =2(4x+y)
2y + 7x + y-1?
-7x - 2y = -3
3x - 2y + 7x + 4y = 3x + 7x - 2y +4y = (3+7)x + (-2+4)y = 10x + 2y
4x + 8 + 7x + 12 = 11x + 20
The answer to the math problem of 5x plus 7x-4x 6 is -12.
Right, 3x-4x+9x-x1. 3x - x = 2x2. 9x-4x = 5x- 2x +5x = 7x
56xy + 2y + 3x
4x+9 = 7x+3 4x-7x = 3-9 -3x = -6 x = 2
As there are no parentheses then the expression stated can be simplified as follows :- 7x - 4x - 9 = 3x - 9 If the parentheses were placed (7x - 4x) - 9 then the result would be the same. If the parentheses were placed 7x - (4x - 9) = 7x - 4x + 9 = 3x + 9.
The standard form is 7x + 2y - 3 = 0
4x+5=7x-8 the ansewr is 3.25
3x + 4x = 7x
3x + (-2 + 4x) = -2 + 7x
5x+2x-3y+y = (5+2)x+(-3+1)y = 7x - 2y
4x + 2y = 12 3x - 2y = 9 Have to use simultaneous equations, so add together to get : 7x = 21 so x = 3 Put it into any part of the equation 4x3 + 2y = 12 12 + 2y = 12 2y = 0 y = 0, x = 3
(14x-2y)+(7x-3y)+(-3x) = 14x-2y+7x-3y-3x =(14+7-3)x-(2+3)y =18x-5y
Subtract by 7x and divide by 2.